Kesesuaian Putusan Pengadilan Agama Ambon Nomor 220/Pdt.G/2021/Pa.Ab Tentang Izin Berpoligami - Iftin Yuninda Hart; La Ode Angga; Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The Marriage Law adheres to the principle of monogamy because the law and religion of the person concerned allows it, a husband can have more than one wife if he meets the requirements.Purposes of the Research: To review the Ambon Religious Court through its decision Number 220/Pdt.G/2021/PA.Ab has given permission to the applicant to carry out polygamy without fulfilling the provisions contained in the Law.Methods of the Research: The writing method is normative juridical, with three approaches, namely the conceptual approach, the statutory approach and the case approach.Results of the Research: The results of this research show that the decision of the Ambon Religious Court Number 220/Pdt.G/2021/PA.Ab which has given permission to the applicant to practice polygamy is contrary to Article 4 paragraph 2 of the Marriage Law.